(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the names of male and female belt clothing used in the dialect of Pidhaytsi region residents is studied. Their semantics, etymology, functioning, word formation peculiarities are defined. The correlation of examined dialects with other Ukrainian dialects is found out.